The changing role of bio-physical and socio-economic drivers in determining livestock distributions: A historical perspective from Kazakhstan. (March 2016) - Robinson, S.; Kerven, C.; Behnke, R.; Kushenov, K.; Milner-Gulland, E.J.
Abstract: Despite worldwide trends towards intensive livestock production, some extensive systems retain comparative advantages, particularly in arid regions. In such variable environments, the extent to which natural pastures can contribute to animal nutrition depends on how livestock are distributed with respect to forage resources in time and space. Animal movements are governed by the interactions of bio-physical, economic and institutional drivers and constraints, all of which are dynamic in time and space, making disentangling the relative importance of different drivers challenging. We examine a large migratory system in central Kazakhstan, using unique long-term data in the context of major socio-economic change, to explore the changing role of bio-physical variables in shaping livestock movement. We explore the determinants of livestock distributions across broad ecological zones in pre-Soviet, Soviet and current time-periods. Differences between zones were examined using Soviet literature, recent interviews with herders and satellite imagery. At the site level, we combined data on livestock locations and density for 2003 and 2012 with bio-physical data from remote sensing. Taken together, these data suggest that the importance of bio-physical variables in determining inter-zonal movements and their timing have decreased over time, whilst the significance of economic and institutional factors appears to have increased. Although resource density may still be a "pull factor" driving movement in some situations, there is evidence that "push factors" such as snow cover, presence of harmful insects and temperature combine with herd size to influence movements between zones, leading to a reduction in the matching between grazing distribution and forage resources. These changes reflect the move to livestock management by small household units owning highly variable numbers of animals. They are representative of global trends in pastoral systems, in which reduction in mobility is linked to declines in collective management institutions, increasing integration of pastoralists in the wider economy and land tenure change. Highlights: We examine historical change in the drivers of livestock movements in Kazakhstan. In the past principal drivers were bio-physical factors such as forage and snow. Livestock movements are now governed by a more complex set of push and pull factors. The role of economic factors such as herd size has grown. Changes are linked to loss of traditional or state institutions supporting mobility.